Learning Disability and Northern Ireland: Achieving Proportionate Universalism through Administrative Data Research - Murphy, Jamie; McBride, Orla; Hanna-Trainor, Lisa; Taggart, Laurence; Shevlin, Mark; Heslop, Pauline; McConkey, Roy; Glover, Gyles (International Journal of Population Data Science, 2018)
Background The Department of Health, Social Services & Public Safety’s policy document ‘Fit and Well – Changing Lives (2012-2022)’ indicates that people with a learning disability (LD) represent one of the most vulnerable and disadvantaged groups in Northern Ireland (NI). Individuals with a LD are more likely to experience major illnesses, to develop them earlier, and die of them sooner, than the general population. Furthermore, the LD population is less likely to get some of the evidence-based annual health checks and treatments they need, and continue to face real barriers in accessing services. At present there is no central register detailing the actual number of individuals with LD in NI. Study aims The study is based on research funded by the ESRC SDAI (ES/P002293/1). It involves the analysis of Northern Ireland Mortality Study (NIMS) data to: Establish the socio-demographic characteristics of the LD population; Profile morbidity and comorbidity of health care problems among individuals with LD; and Explore the causes of death among the NI LD community. Results and Conclusions Preliminary study findings will be available by June 2018. Findings will be of particular interest to a range of government departments, trusts and learning disability support groups.